An evaluation study of research efficiency of the Guangzhou institute of respiratory diseases based on malmquist index - Liao, Jian-Feng; Wang, Juan; Liang, Liang; Wu, Yong-Ding; Huang, Mei-Juan; Liu, Tian-Qiang; Zhou, Lin; Wang, Xin-Wang (Journal of Thoracic Disease, 2016)
Background: This study aimed to analyze the dynamic changes of the scientific research innovation efficiency of Guangzhou Institute of Respiratory Diseases (GIRD) during the year 2009–2013 to explore the reason for these changes and give some suggestions on how to improve the overall efficiency of the Institute. Methods: The panel data used in this study were taken from 19 research teams of GIRD during 2009 to 2013. Data envelopment analysis (DEA) based on Malmquist index (MI) was used to analyze the performance of each research team in terms of productivity changes over time. Data were analyzed using DEAP 2.1 software. Results: The annual average increase rate of total factor productivity (TFP), technological progress, technical efficiency, pure technical efficiency, and scale efficiency was 30.4%, 22.5% , 6.4%, 0.9%, and 5.4%, respectively from 2009 to 2013. The scientific research innovation efficiency of the GIRD was generally high and kept on growing. The increase of TFP was mainly caused by the progress of tech, the descending of TFP in some teams should be mainly attributable to the declining pure technical efficiency, and scale efficiency on the whole, maintaining a stable growth at a low speed. Conclusions: To achieve higher scientific research innovation, GIRD not only needs to further improve the management level and introduce advanced management mode, but also needs to focus on optimization of resource allocation, as well as to strengthen the talent introduction, and continue to maintain the absorption of new technologies and innovation.